Pengaruh Keselamatan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Karyawan Bagian Produksi Mebel Azia - Mardhatila Fitri Sopali; Putri Azizi (Universitas 45 Surabaya, 2025)
This research aims to examine the influence of work safety and Work Environment on Employee Performance through Job Satisfaction as Intervening variables using secondary data obtained by distributed questionnaires to 32 employees who were used as respondents on Furniture Good Luck. In this research, analytical tools are used Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of this research show that work safety positive and significant effect on Job Satisfaction. The work environment has a positive and significant effect on Job satisfaction. Work safety has no significant effect on Employee Performance. The work environment matters positive and significant on employee performance. Satisfaction work has a positive and significant effect on performance Employee. Work safety has no significant effect on Employee Performance through Job Satisfaction as an intervening variable. The work environment has a positive and significant effect on Employee Performance through Job Satisfaction as an intervening variable.